The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jseint.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Minimal clinically important difference, substantial clinical benefit, and patient acceptable symptom state of PROMIS upper extremity after total shoulder arthroplasty

Abstract: Background The Patient-Reported Outcomes Measurement Information System minimal clinically important difference (PROMIS MCID), substantial clinical benefit (SCB), and patient acceptable symptom state (PASS) of patient-reported outcome measures provide clinical significance to patient-reported outcome measures scores. The goal of this study is to measure the MCID, SCB, and PASS of PROMIS Upper Extremity v2.0 (PROMIS UE) in patients undergoing total shoulder arthroplasty (TSA). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…22,23 Previous crosssectional studies 11,12,[24][25][26][27][28][29][30][31] have shown a strong correlation between PROMIS UE CAT and legacy instruments across a spectrum of common orthopedic conditions and procedures. However, there are fewer longitudinal correlation studies 19,21,[32][33][34][35][36] in the literature and none in patients undergoing TSA. We showed that PROMIS UE CAT is sensitive to functional improvements in patients undergoing shoulder Fourth, we did not include all the available patient-reported outcome (PRO) instruments described for shoulder arthroplasty due to logistic issues with conducting the study and maintaining patient participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Previous crosssectional studies 11,12,[24][25][26][27][28][29][30][31] have shown a strong correlation between PROMIS UE CAT and legacy instruments across a spectrum of common orthopedic conditions and procedures. However, there are fewer longitudinal correlation studies 19,21,[32][33][34][35][36] in the literature and none in patients undergoing TSA. We showed that PROMIS UE CAT is sensitive to functional improvements in patients undergoing shoulder Fourth, we did not include all the available patient-reported outcome (PRO) instruments described for shoulder arthroplasty due to logistic issues with conducting the study and maintaining patient participation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross‐sectional studies 11,12,24–31 have shown a strong correlation between PROMIS UE CAT and legacy instruments across a spectrum of common orthopedic conditions and procedures. However, there are fewer longitudinal correlation studies 19,21,32–36 in the literature and none in patients undergoing TSA. We showed that PROMIS UE CAT is sensitive to functional improvements in patients undergoing shoulder arthroplasty as early as 6 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search of the PubMed/MEDLINE databases was used to identify studies examining PROMIS assessments in orthopaedic surgery patients. Studies were included in the anchor-based analyses if they calculated anchor-based thresholds for PROMIS Physical Function for THA, TKA, PLF, ACLR, and APM or the PROMIS Upper Extremity for TSA and RCR [3, 10-12, 16, 18, 23, 24, 29, 34, 37].…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Patient Acceptable Symptom State (PASS) ( 63 , 64 , 66 ) gathers patient perspective about the satisfaction a patient has with their current health state, considering an acceptable level of symptoms, activities of daily living, and function that results in a satisfactory assessment of health. There are various version of the PASS, but most use a dichotomous response scale of “yes” or “no.” Describing the level of satisfaction a patient has with their state of health at the end of care or at the end of participation in a research study warrants consideration as a clinically meaningful research outcome ( 65 , 67 ).…”
Section: Prom Analysis and Interpretationmentioning
confidence: 99%